2021
DOI: 10.1007/s00246-021-02577-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Incidence of Kawasaki Disease in a North American Community: A Population-Based Study

Abstract: To assess the longitudinal incidence of Kawasaki disease (KD) within the well-defined predominantly White population of Olmsted County, MN. This retrospective cohort study used a population-based medical record linkage system and manual chart reviews to identify children with KD in Olmsted County, MN between January 1, 1979-December 31, 2016. Age- and gender-adjusted incidence rates were calculated using the 2010 U.S. White population. 124 children with KD were confirmed during the study period (median age 3.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Indeed, 73.50% of the cases included in this review were males. This is in accordance with previous research, which showed that KD is more common in boys, with a male:female ratio of about 1.6:1 [105,106]. Furthermore, according to Nakamura et al, males suffering from cardiac complications caused by KD experience a higher mortality rate in comparison to the general population, whereas the mortality rates for females with complications and for both males and females without complications were not increased [94].…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, 73.50% of the cases included in this review were males. This is in accordance with previous research, which showed that KD is more common in boys, with a male:female ratio of about 1.6:1 [105,106]. Furthermore, according to Nakamura et al, males suffering from cardiac complications caused by KD experience a higher mortality rate in comparison to the general population, whereas the mortality rates for females with complications and for both males and females without complications were not increased [94].…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of suspected antecedent KD in young adults with suspected ACS is 5% and 7.4% according to Daniels et al and the present study (Table 3), respectively. Given its occurrence in genetically susceptible individuals (18), KD is more prevalent in children younger than 5 years old of the present cohort [20 (19) vs. 80 (4) per million children <5 years old]; however, the prevalence difference of antecedent KD is smaller than expected. This may be due to a multi-factor phenomenon, including genetic diversity, medical source accessibility, diet habits, and self-health management awareness (20).…”
Section: Different Incidence Different Prevalencementioning
confidence: 77%